2008
DOI: 10.1097/aud.0b013e31816453a6
|View full text |Cite
|
Sign up to set email alerts
|

Client-Based Adjustments of Hearing Aid Gain: The Effect of Different Control Configurations

Abstract: Client-based adjustments of hearing aid gain provide a reliable method of individual fine-tuning. The results also showed that a biased correction of amplification is reached via self-adjustment within one session, which reduces the effectiveness of fine-tuning in a traditional clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 23 publications
4
74
2
3
Order By: Relevance
“…This would suggest that NAL-NL2 makes a better general starting point. As demonstrated in recent studies, starting from an appropriately prescribed baseline response is important as self-adjustments, or training of hearing aids, are biased by the starting point (Dreschler, Keidser, Convery, & Dillon, 2008;Keidsser, Convery, & Dillon, 2008a;Mueller, Hornsby, & Weber, 2008), which means that audiologist-driven finetuning probably is too. Because hearing aids are more likely to be equipped with a volume than a tone control, verifying the prescribed gain-frequency response shape, which results primarily from the speech intelligibility modeling in the optimization process described in Dillon et al (in press), should have highest priority in future evaluation studies.…”
Section: Evaluation and Future Researchmentioning
confidence: 99%
“…This would suggest that NAL-NL2 makes a better general starting point. As demonstrated in recent studies, starting from an appropriately prescribed baseline response is important as self-adjustments, or training of hearing aids, are biased by the starting point (Dreschler, Keidser, Convery, & Dillon, 2008;Keidsser, Convery, & Dillon, 2008a;Mueller, Hornsby, & Weber, 2008), which means that audiologist-driven finetuning probably is too. Because hearing aids are more likely to be equipped with a volume than a tone control, verifying the prescribed gain-frequency response shape, which results primarily from the speech intelligibility modeling in the optimization process described in Dillon et al (in press), should have highest priority in future evaluation studies.…”
Section: Evaluation and Future Researchmentioning
confidence: 99%
“…The primary aim of a hearing aid is, based on the individual hearing loss, to provide the hearing impaired person an audible signal by the gain in the hearing aid. In addition, modern hearing aids also compensates to some extent for suprathreshold deficits using compression, division in multiple frequency-bands, and signal processing strategies to enhance the desired signal (speech) or decrease the unwanted sound (noise), often differently in different acoustical environments (Dreschler et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There are studies indicating that hearing aid users and normal hearing listeners rate annoying sounds as equally annoying (Palmer et al, 2006;Keidser et al, 2007;Keidser et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Convery et al (2005), Keidser, Dillon, et al (2008) and Smeds et al (2006) also found that the preferred gain-frequency response varied with listening conditions. Dreschler, Keidser, Convery, and Dillon (2008) found overall gain and response slopes across six test conditions, including speech in quiet and in speech noise and nonspeech noise, varied significantly from NAL-RP settings. They found preferred gain to be lower for louder sounds or in conditions where only noise was present.…”
Section: Pico Question Nomentioning
confidence: 86%
“…Conclusion: Overall, there is evidence that users are able to discriminate between various responses and manipulate up to four parameters (Dreschler et al, 2008) to train the hearing aids to preferred settings and that hearing aid users would prefer trained responses to untrained responses (Dreschler et al, 2008;Keidser, Dillon, et al, 2008;Mueller et al, 2008;Zakis et al, 2007). These are Level 3 and Level 4 evidence, resulting in an overall Grade "B" recommendation (Wong & Hickson, 2012).…”
Section: How Well Does a Hearing Aid Algorithm Converge To The Users'mentioning
confidence: 99%